Cheapness and (labor-)power: The role of early modern Brazilian sugar plantations in the racializing Capitalocene. (February 2020) - Eichen, Joshua R
This essay looks at the historical geography of sugar plantations in Northeast Brazil during the 16th- and 17th-centuries to critique the spatio-temporality of the discourse of the Anthropocene. I argue that sugar plantations were key places in early systemic cycles of capital accumulation with their grim calculus of cheap labor-power and acceptable deaths. Sugar plantations were simultaneously prototypical racializing state actors and part of the emergent relations of capital changing the climate. With their rationalized, time-disciplined labor for processing cane into sugar, plantations were not only fundamentally proto-industrial sites, but also one of capital's laboratories of modernity. They were primordial sites of proletarianization, of spatio-temporal patterns that repopulated the Americas and central in the production not of the Anthropocene but of the racializing Capitalocene.